When AI intervene clinical decision-making: the influence of organisational support, cognitive load, and perceived autonomy - Isparan, Shanthi; Ai-Na, Seow (Academica Press Solutions, 2025)
The integration of Artificial Intelligence (AI) in healthcare holds the potential to optimise clinical decisionmaking. However, the effectiveness of AI intervention in clinical decision-making can influence the ability of healthcare professionals to effectively process and apply AI-generated recommendations. This research examines the influence of organisational support (OS) on cognitive load (CL) and its impact on the effectiveness of AI-assisted clinical decision-making. The study further investigates the mediating role of cognitive load and explores the moderating effect of perceived autonomy (PA). Organisational Support Theory (OST), Cognitive Load Theory (CLT), and Self-Determination Theory (SDT) are used to support these dynamics. The targeted respondents are medical doctors in Malaysia, and data are analysed using Partial Least Squares Structural Equation Modeling (PLSSEM). It is expected that the increased OS will reduce CL, leading to improved AI-assisted clinical decision-making, with PA strengthening this relationship. The findings offer actionable insights for healthcare institutions, suggesting strategies to strengthen AI implementation, streamline workflows, and enhance clinical decision-making.